Gandhian thought - Ravindra Kumar (New Delhi, 2006)
Foreword Introduction Abbreviations Gandhi and Religion Mahatma Gandhi and Politics Gandhism and Purpose and Goal of Education Gandhi: Non-violence and Democracy Religion in Politics: Constructive or Destructive Gandhi, Education and Peace The Significance of Gandhism in the Establishment of Peace Gandhism and Conflict Resolution at the Close of Twentieth Century Relevance of Gandhism in the Modern Polity Gandhi's Legacy and Nuclearized States of South Asia Gandhism, Peace Education and Construction of a Sustainable Culture of Peace On Problem of Communalism (A) Self-Supporting Education (B) Rights or Duties (C) Peace Brigades (D) Volunteer Corps Glossary of Indian Terms Who's who Index
Keywords: "Gandhi,M.K."